Identification of Volatile Compounds coming from Starch-Base Biopolymer intended to Food Contact by GC-MS - Osorio Monsalve, Jazmin; Aznar, Margarita; Nerín, Cristina (Jornada de Jóvenes Investigadores del I3A, 2018)
Starch-base biopolymers are commonly used as food contact materials. In this work, the volatile compounds of a starch-base material and its migration to ethanol 95% food simulant were determined by GC-MS.  A total of 35 compounds were detected in the material, 5 of them were also detected in migration.